The Impact of Mental Health on Employee Productivity: Mediating Roles of Job Engagement and Cognitive Functioning - Ahmed, Md. Shakil; Urmi, Sadia Ahmed; Rahman, Md Yeanur; Ahamed, Rasel; Hossain, Sagor; Uddin, Md Bashir (Yayasan Sinergi Kawula Muda, 2026)
This study investigates the impact of mental health on employee productivity, focusing on the mediating roles of job engagement and cognitive functioning. It aims to clarify how psychological and cognitive resources work together to convert mental health into increased productivity at work. A quantitative research design was employed with 324 employees in 10 manufacturing companies in Dhaka, Bangladesh. The proposed direct, indirect, and sequential effects were tested using SPSS v27 and bootstrapped mediation analysis with Structural Equation Modeling (SEM) using AMOS v24. The findings indicate that mental health has a significant positive direct effect on employee productivity (β = 0.244, p = 0.007) and significantly influences job engagement (β = 0.741, p < 0.001) and cognitive functioning (β = 0.362, p < 0.001). While the indirect effect on productivity through job engagement alone was positive but not statistically significant (β = 0.097, p = 0.207), cognitive functioning significantly mediated this relationship (β = 0.073, p = 0.037). Moreover, a significant sequential mediation pathway was observed (MH → JE → CF → EP; β = 0.068, p = 0.039), demonstrating that job engagement enhances cognitive functioning, which subsequently improves productivity. In order to establish a cohesive framework that links affective and cognitive dynamics, this study combines the ideas of the Job Demands–Resources (JD-R) and the Conservation of Resources (COR). To our knowledge, this is among the few empirical studies from a developing-country context to examine both dual and sequential mediation effects in this relationship.